Antibiotic adherence and treatment completion associated with partial oral therapy versus all intravenous therapy in patients with serious Staphylococcus aureus infections - Alexandra Craig; Katherine C. Shihadeh; Bryan C. Knepper; Whitney Miller; Heather L. Young; Deborah Aragon; Timothy C. Jenkins (BMC Infectious Diseases)
Abstract Background Partial oral antibiotic therapy is a safe and effective alternative to all intravenous (IV) therapy for serious Staphylococcus aureus infections; however, antibiotic adherence and treatment completion rates associated with partial oral therapy outside of clinical trials are unknown. Methods This was a retrospective study of adults hospitalized with S. aureus bacteremia, endocarditis, or bone or joint infection. Co-primary outcomes of antibiotic adherence and treatment completion were compared between patients who transitioned to oral antibiotics during treatment or received all IV therapy. Factors associated with lack of treatment completion were evaluated by logistic regression. Results Of 249 patients, 148 (59%) and 101 (41%) were treated with partial oral or all IV therapy, respectively. Use of partial oral therapy was more common for bone or joint (73% of cases) than bloodstream infections (21% of cases). Antibiotic adherence was similar between the partial oral and all IV groups; 90% and 98% of patients completed the planned course, respectively (p = 0.38). By logistic regression, partial oral therapy was independently associated with lack of treatment completion (odds ratio 4.53 [95%CI 1.0–20.6]). Clinical failure occurred in 26% and 25% of patients who received partial oral and all IV therapy, respectively (p = 0.87). Conclusions In clinical practice, a high proportion of patients treated with partial oral therapy for serious S. aureus infections completed treatment, but partial oral therapy was an independent risk factor for failure to complete treatment. These findings highlight the importance of identifying and addressing barriers to adherence when considering oral therapy.